2020
DOI: 10.1021/acs.est.9b05565
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Per- and Polyfluoroalkyl Substances (PFAS) with Advanced Reduction Processes (ARPs): A Critical Review

Abstract: Advanced reduction processes (ARPs) have emerged as a promising method for destruction of persistent perand polyfluoroalkyl substances (PFAS) in water due to the generation of short-lived and highly reductive hydrated electrons (e aq − ). This study provides a critical review on the mechanisms and performance of reductive destruction of PFAS with e aq − . Unique properties of e aq − and its generation in different ARP systems, particularly UV/sulfite and UV/iodide, are overviewed. Different degradation mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
212
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 317 publications
(219 citation statements)
references
References 124 publications
7
212
0
Order By: Relevance
“…72,[95][96][97] In this context, e -(aq) have received renewed attention with the report of e -(aq) mediated degradation of the emerging per-and polyfluoroalkyl substances (PFAS). 45,46,52,98,99 The results of this study also imply that e -(aq)generating engineered systems for water treatment would likely be effective for degrading SCCPs, and provides further support to the notion that e -(aq) is a versatile PPRI for degrading persistent organic pollutants.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…72,[95][96][97] In this context, e -(aq) have received renewed attention with the report of e -(aq) mediated degradation of the emerging per-and polyfluoroalkyl substances (PFAS). 45,46,52,98,99 The results of this study also imply that e -(aq)generating engineered systems for water treatment would likely be effective for degrading SCCPs, and provides further support to the notion that e -(aq) is a versatile PPRI for degrading persistent organic pollutants.…”
supporting
confidence: 64%
“…In addition, the majority of previous research has focused on engineered systems for water treatment, not environmentally-relevant processes. 40,44,46,[51][52][53][54][55][56] The aim of this study was therefore to determine the reactivity of SCCPs with e -(aq), and compare it to •OH-mediated degradation. This knowledge will provide additional insights into their photochemical fate in surface waters.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced reduction processes (ARPs), reductive metals (e.g., zero-valent iron (ZVI)), hydride radicals (H·) and most notably hydrated electrons (E 0 = −2.9 V) have been used to achieve the effective cleavage of C−F bonds in PFASs [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. The investigation of PFAS reduction reactions have shown that they are sensitive towards the choice of reagents, their concentrations and reaction times as well as pH value of the solution [ 74 , 75 , 76 ], thus can show variable efficiencies. Hereafter, we give a detailed overview of recent developments of PFAS-degradation based on reductive defluorination.…”
Section: State-of-the-art Liquid Reactionsmentioning
confidence: 99%
“…Oxidative and photochemical methods were often investigated in several research projects in the past [ 62 , 76 , 87 ]. The photochemical reduction was mainly performed with UV light and free reducing radicals formed from sulphite (SO 3 2- ), but other inorganic and organic compounds were also used.…”
Section: State-of-the-art Liquid Reactionsmentioning
confidence: 99%
See 1 more Smart Citation